Two Symmetrical Maxillary First Molars with Two Disto-Buccal Root Canals - Ghoddusi, Jamileh; Javidi, Maryam; Vatanpour, Mahdi (Iranian Endodontic Journal, 2008)
INTRODUCTION: This article describes the diagnosis and treatment of two symmetrical maxillary first molars with two canals in their distobuccal roots. A 32-year-old female had an emergency treatment because of the pain in tooth #16. On the second visit after accessing the pulp chamber and detecting three major canals (MB, DB, and P) and exploring the 4th canal (MB2), we noted that there was a 5th canal in the distobuccal root. Also, necrosis was found in the same patient after examining the tooth #26 which was severely decayed. Then after preparing the access cavity, the same order of orifices was found in tooth #16. An electronic apex locator was utilized to ensure that a perforation of the pulpal floor had not occurred. Working films confirmed the presence of an additional canal in distobuccal root.